First step to environmentally sustainable endoscopy practice: a prospective study of minimizing multiple device use during screening colonoscopy at a large tertiary center - Harne, Prateek S.; Harne, Vaishali; Rehman, Asad; Thosani, Nirav; Desai, Madhav (Endoscopy, 2024)
The healthcare sector generates 8% of greenhouse gas emissions in the USA, of which gastrointestinal (GI) endoscopy is the third largest contributor. Single-use tools are a major contributor to modifiable waste generation during GI endoscopy. Through a quality improvement initiative, we aimed to reduce endoscopy waste by urging gastroenterologists to be mindful of tools used during polypectomies by avoiding using multiple tools.We discussed green endoscopy initiatives in monthly journal club and business meetings. Over 14 weeks, 210 patients were included in the pre-intervention group and 112 in the post-intervention group.At baseline, 34% of colonoscopies required no intervention, 32% required one tool (either biopsy forceps or a snare), and 33% required multiple tools. After the intervention, the use of just one tool increased (17 percentage point increase; P=0.003) and the use of multiple tools decreased significantly (16 percentage point decrease; P=0.002). The odds ratio for use of a single tool compared with multiple tools after the intervention was 3.0 (95%CI 1.6 to 5.5; P=0.005).This single-center quality improvement study noted a significant change in practice patterns favoring the use of a single tool over multiple tools during colonoscopies after an environmentally conscious practice intervention was applied. This intervention can be readily applied to reduce endoscopy-related waste.